New life of the Classics: The current situation of intralingual translations in Old Polish Literature - Kraska, Dominika (Melusine. Old Literature and Culture, 2025)
The article analyzes the current state of intralingual translations in the context of Old Polish literature. The author discusses selected examples of modernized classical texts, highlighting their diverse purposes (educational, theatrical) and the lack of methodological and editorial coherence. Special emphasis is placed on a comparison with French modernization practices, which – unlike the Polish situation – are more systematized and institutionalized. The article advocates for the development of an organized research and editorial framework for intralingual translations in Poland and suggests adapting foreign strategies to local needs.